The Impact of Sustainability Practices and Customer Satisfaction on Customer Loyalty in Major Coffee Chains in Indonesia - Kuncorosidi Kuncorosidi; Anadyas Putri Mulya Wijaya; Jojo Jojo (DIMENSIA (Diskursus Ilmu Manajemen STIESA), 2024)
This study aims to analyze the impact of sustainability practices and customer satisfaction on customer loyalty in major coffee chains in Indonesia. The data analyzed was the result of a questionnaire filled out by 100 respondents who had bought Kopi Janji Jiwa. This study uses descriptive methods and quantitative research types. Using primary data, namely through questionnaires, and secondary data, namely through literature study sources. In sampling, the techniques used are non-probability sampling and purposive sampling techniques, which involve distributing questionnaires to respondents. The data analysis technique used in this study is multiple regression analysis, using classical assumption tests and hypothesis tests. The results of this study prove that there is a simultaneous overall influence between the impact of sustainability practices and customer satisfaction on customer loyalty. Partially, the impact of sustainability practices has a significant effect on customer loyalty, while partially, customer satisfaction has no significant effect on customer loyalty.